A Study Between Perfectionism And Thinking Style Among Gifted And Talented Muslim Students In Malaysia - Amnah Zanariah Abd Razak; Amirah Zainun; Nur Fazidah Asmuje; Syazwani Md. Sallehan (Usuli Faqih Research Centre PLT., 2024)
Non-Indexed Publication